Teaching Subjective Construal and Related Constructions with SCOBAs. (10th June 2021) - Masuda, Kyoko; Ohta, Amy Snyder
Abstract : Japanese and English have substantial typological differences, including different construal patterns. Construal patterns reflect linguistic framing of events, more objectively or more subjectively, depending on whether the speaker is understood as a separate part of the scene or as merged with the scene. English frames events using objective construal more often than subjective construal; Japanese overwhelmingly prefers subjective construal. Understanding construal is critical for Japanese L2 learners, yet overlooked in Japanese pedagogy. This paper considers how SCOBAs (Schema of a Complete Orienting Basis of an Action) can be used in Concept-Based Language Instruction (C-BLI) to teach construal. The first SCOBAs introduced visualize construal concepts; subsequent SCOBAs depict how Japanese subjective construal relates to other constructions, including the non-use of 'I', motion verbs, verbs meaning 'give', and psychological predicates. We also discuss approaches to promoting internalization of the concepts via a variety of dialogic tasks and application exercises.